Mysteries of the Trade? Skill-Specific Local Agglomeration Economies - Martin Andersson; Johan P. Larsson (Research Institute of Industrial Economics (IFN), 2020)
Using longitudinal Swedish data, we document robust evidence of highly local spillovers between individuals in similar occupations. The results are consistent with the existence of knowledge spillovers between workers performing similar work tasks in the same city-district. We further demonstrate less distance-sensitive benefits of working in diverse districts and regions, characterized by high density of employees in other occupations. The diversity benefits exist only in metropolitan areas and pertain to workers performing advanced services or non-routine work tasks.
Keywords: R10; R12; J24; 330; Agglomeration economies; Wages; Spillovers; Attenuation; Clusters; Economic proximity; Relatedness